Shooting Mechanisms in Nature: A Systematic Review - Sakes, Aimée; van der Wiel, Marleen; Henselmans, Paul W. J.; van Leeuwen, Johan L.; Dodou, Dimitra; Breedveld, Paul (PloS one, 2016)
In nature, shooting mechanisms are used for a variety of purposes, including prey capture, defense, and reproduction. This review offers insight into the working principles of shooting mechanisms in fungi, plants, and animals in the light of the specific functional demands that these mechanisms fulfill. We systematically searched the literature using Scopus and Web of Knowledge to retrieve articles about solid projectiles that either are produced in the body of the organism or belong to the body and undergo a ballistic phase. The shooting mechanisms were categorized based on the energy management prior to and during shooting. Shooting mechanisms were identified with projectile masses ranging from 1·10-9 mg in spores of the fungal phyla Ascomycota and Zygomycota to approximately 10,300 mg for the ballistic tongue of the toad Bufo alvarius. The energy for shooting is generated through osmosis in fungi, plants, and animals or muscle contraction in animals. Osmosis can be induced by water condensation on the system (in fungi), or water absorption in the system (reaching critical pressures up to 15.4 atmospheres; observed in fungi, plants, and animals), or water evaporation from the system (reaching up to -197 atmospheres; observed in plants and fungi). The generated energy is stored as elastic (potential) energy in cell walls in fungi and plants and in elastic structures in animals, with two exceptions: (1) in the momentum catapult of Basidiomycota the energy is stored in a stalk (hilum) by compression of the spore and droplets and (2) in Sphagnum energy is mainly stored in compressed air. Finally, the stored energy is transformed into kinetic energy of the projectile using a catapult mechanism delivering up to 4,137 J/kg in the osmotic shooting mechanism in cnidarians and 1,269 J/kg in the muscle-powered appendage strike of the mantis shrimp Odontodactylus scyllarus. The launch accelerations range from 6.6g in the frog Rana pipiens to 5,413,000g in cnidarians, the launch velocities from 0.1 m/s in the fungal phylum Basidiomycota to 237 m/s in the mulberry Morus alba, and the launch distances from a few thousands of a millimeter in Basidiomycota to 60 m in the rainforest tree Tetraberlinia moreliana. The mass-specific power outputs range from 0.28 W/kg in the water evaporation mechanism in Basidiomycota to 1.97·109 W/kg in cnidarians using water absorption as energy source. The magnitude of accelerations involved in shooting is generally scale-dependent with the smaller the systems, discharging the microscale projectiles, generating the highest accelerations. The mass-specific power output is also scale dependent, with smaller mechanisms being able to release the energy for shooting faster than larger mechanisms, whereas the mass-specific work delivered by the shooting mechanism is mostly independent of the scale of the shooting mechanism. Higher mass-specific work-values are observed in osmosis-powered shooting mechanisms (≤ 4,137 J/kg) when compared to muscle-powered mechanisms (≤ 1,269 J/kg). The achieved launch parameters acceleration, velocity, and distance, as well as the associated delivered power output and work, thus depend on the working principle and scale of the shooting mechanism.